Efectos del programa de actividades de psicomotricidad en la coordinación gruesa en niños de cinco años de la Institución Educativa Inicial N°476 Cuna Jardín los Arbolitos, Iquitos 2024 - Maca Tapullima, Ketty Reyna (2024)
The purpose of this research is to evaluate the effect of the psychomotor activities program on gross coordination in five-year-old children of the Initial Educational Institution N°476 Cuna Jardín los Arbolitos, Iquitos 2024. In this study the type of research was used quantitative, likewise the quasi-experimental design was used. The population under study consisted of all five-year-old children. Observation was used as a technique for data collection and as an observation guide instrument, this instrument was validated by three experts on the subject, for the reliability of the instruments they were evaluated with a pilot test, using the Cronbach's Alpha test. The statistical results confirm that the program had a significant effect. The t-test for independent samples yielded a value of t = 6.432 with a p-value = 0.000, which allowed us to reject the null hypothesis and accept the alternative hypothesis. It is concluded that the program not only improved the children's gross coordination compared to the control group, but also provides solid evidence about the importance of the implementation of psychomotor programs in child development.